TANTANGAN DAN STRATEGI GURU SD MUSI RAWAS DALAM OPTIMALISASI TIK ERA INDUSTRI 4.0 - Rofiq, Moh; Iswatiningsih, Daroe (Penerbit Lafadz Jaya, 2025)
This study aims to identify the challenges and strategies faced by elementary school teachers in optimizing the use of Information and Communication Technology (ICT) in the learning process during the Industrial Revolution 4.0 era. The background of this study is rooted in the significant transformation of education due to digitalization, which demands a shift in both the roles of teachers and learning systems. This research employed a qualitative descriptive approach with data collected through in-depth interviews, observation, and documentation involving 10 teachers from five elementary schools in Sumber Harta District, Musi Rawas Regency. The findings revealed key challenges such as limited infrastructure, low digital literacy, and the lack of continuous training. Nevertheless, teachers demonstrated adaptive strategies by utilizing free digital tools, fostering peer collaboration, and implementing project-based learning. Support from school principals and learning communities proved to be significant contributing factors. This study concludes that collaborative efforts, policies that prioritize teacher capacity building, and equitable technology access are crucial to bridging the digital divide in primary education.